Sequence and expression analysis of the spermatogenesis-specific gene cognates, wampa and Prosα6T, in Drosophila suzukii - Xia, Qinwen; Tariq, Kaleem; Hahn, Daniel A.; Handler, Alfred M. (Genetica, 2023)
The sterile insect technique (SIT) is a highly effective biologically-based method for the population suppression of highly invasive insect pests of medical and agricultural importance. The efficacy of SIT could be significantly enhanced, however, by improved methods of male sterilization that avoid the fitness costs of irradiation. An alternative sterilization method is possible by gene-editing that targets genes essential for sperm maturation and motility, rendering them nonfunctional, similar to the CRISPR-Cas9 targeting of β2-tubulin in the genetic model system, Drosophila melanogaster . However, since genetic strategies for sterility are susceptible to breakdown or resistance in mass-reared populations, alternative targets for sterility are important for redundancy or strain replacement. Here we have identified and characterized the sequence and transcriptional expression of two genes in a Florida strain of Drosophila suzukii , that are cognates of the D. melanogaster spermatocyte-specific genes wampa and Prosalpha6T . Wampa encodes a coiled-coil dynein subunit required for axonemal assembly, and the proteasome subunit gene, Prosalpha6T , is required for spermatid individualization and nuclear maturation. The reading frames of these genes differed from their NCBI database entries derived from a D. suzukii California strain by 44 and 8 nucleotide substitutions/polymorphisms, respectively, though all substitutions were synonymous resulting in identical peptide sequences. Expression of both genes is predominant in the male testis, and they share similar transcriptional profiles in adult males with β2-tubulin . Their amino acid sequences are highly conserved in dipteran species, including pest species subject to SIT control, supporting their potential use in targeted male sterilization strategies.